Prevalence of Helminthiasis in Beef Cattle in West Muna Regency - Wa Ode Umrawati Latif; Farra Sasmita; Sri Fauzia (Pascasarjana Universitas Sulawesi Tenggara, 2023)
West Muna Regency is one of the areas in Southeast Sulawesi Province which has a cattle population of 33.900 heads in 2021. This livestock business requires infrastructure to ensure the health of livestock to avoid disease. The disease that is often found in animal husbandry is helminthiasis (helminthiasis). Worms are a disease caused by the presence of worms that infect the animal's body both in the digestive, respiratory, liver and other body parts. The research was conducted in West Muna Regency in October-November 2022. This research used a quantitative research method with a secondary data analysis approach. Secondary data was obtained from helminthiasis case data and the cattle population was obtained from data from the West Muna Agricultural Service Center. Data analysis in this study used descriptive analysis which aimed to describe the prevalence of helminthiasis in cattle. Based on the results of the study, it was found that the prevalence of helminthiasis in cattle in West Muna Regency in 2022 has an average value of 24%.